Osos vaqueros en el páramo incomún: Hacia una conservación cosmopolitica del oso andino en el páramo de Chingaza, Colombia - Martínez-Medina, Santiago (2022)
Since the end of the 20th century, the emblematic Andean bear has become the protagonist of new scientific and political conservation agendas in the Colombian Andes. This article presents an ontological, multispecies, and historical analysis of the encounters between different forms of knowing nature in the páramo of Chingaza, a protected area east of the city of Bogotá. Programs for the conservation of the only species of bear described by taxonomists in South America have raised tensions with campesino communities who give accounts of the existence of two types of bears. Without seeking to “correct” the natural scientists who discard this possibility, this article aims to open up conceptual possibilities that understand the bear as a contact entity in an also multiple páramo.. Combining ethnographic and historical methods, we trace the longer and silenced trajectories behind the practices that support Andean bear conservation in Chingaza today. Observing a recent reorientation in scientific and institutional dialogues with peasant communities, we suggest a shift towards a ‘cosmopolitical’ conservation capable of articulating the worlds of the campesinos of the high mountains.